Pengukuran Pengungkapan Kinerja Keberlanjutan pada Perusahaan Sektor Perbankan Berdasarkan Peraturan Otoritas Jasa Keuangan Nomor 51/Pojk.03/2017 - Adinda Permata Hati (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
This study examined the conformity of Indonesian banking sustainability reports with the indicators outlined in Financial Services Authority Regulation No. 51/POJK.03/2017. This study employed a descriptive approach, examining banking sector companies listed on the Indonesia Stock Exchange in 2023. The data collection method used is documentation. Data was collected through documentation. The study found that while all banks issued sustainability reports, compliance with POJK No. 51/POJK.03/2017 was partial. Bank CIMB Niaga (National Private Bank), Bank Jatim (Regional Development Bank), and Bank BTN (SOE Bank) achieved the highest scores within their respective groups. National Private Banks demonstrated higher compliance compared to SOEs and Regional Development Banks. Overall, all banks were classified as partially applied.